Peran kecerdasan buatan dalam pemetaan risiko ekonomi makro - Jailani, Mohammad Shohibul Fajar (Maliki Interdisciplinary Journal, 2025)
The development of Artificial Intelligence (AI) has revolutionized approaches to macroeconomic analysis, particularly in mapping complex, dynamic, and multidimensional risks. This article explores the role of AI in identifying, forecasting, and managing macroeconomic risks through the application of machine learning algorithms, natural language processing, and other predictive modeling systems. The study examines AI’s contribution to forecasting key macroeconomic indicators such as inflation and economic growth, as well as its use in nowcasting and early warning systems for systemic crises. In the Indonesian context, AI has begun to be integrated into the measurement of economic uncertainty through text data processing of online news sources. Despite its promising potential, the application of AI still faces challenges such as data limitations, ethical issues, and the need for model interpretability. Using a descriptive-qualitative approach and literature review from national (SINTA) and international (Scopus) journals, this article highlights the importance of cross-sector collaboration and good governance in optimizing the role of AI in strengthening macroeconomic resilience both nationally and globally.